“Actividades Lúdicas para el desarrollo de la Motricidad Fina en niños de Educación Inicial” - Inaquiza Camacho, Estefania Lizbeth (2024)
Fine motor skills are crucial for the early development of children, as they influence skills such as writing or handling small objects; however, an insufficient development of fine motor skills is observed inserved in children in early childhood education, possibly due to the lack of activities specifically designed to stimulate motor skills. The main objective is to design and implement a series of play activities based on the constructivist pedagogical approach and Jean Piaget's methodology, aimed at improving children's fine motor skills in early childhood education. In this way, the play activities become pedagogical tools that support the child's emotional, motor and cognitive development. A qualitative approach was used, together with a field and the inductive method. Techniques and instruments such as observation and interviewing were used, with various playful activities designed such as the use of modelling clay, puzzles, drawing and cutting out, for which a group of children of Early Education was selected, with whom these activities were carried out during a determined period, observing and registering their progress. The results showed a significant improvement in the fine motor skills of the participating children, observing an increase in the ability to perform tasks that require manual precision, such as grasping small objects and hand-eye coordination. It is advisable to integrate this type of activities within the educational curriculum to promote a comprehensive development in children, therefore, this project benefits and awakens interest in teachers and students of the various educational units of the canton Pujilí, Guangaje parish.